1983
DOI: 10.1111/j.1471-4159.1983.tb11316.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Applications of a Solid‐Phase Radioimmunoassay for the P0 Protein of Peripheral Myelin

Abstract: This is the first report of a quantitative radioimmunoassay for PO. The assay uses antigen-coated plastic microwells, with antibody binding detected by 125I-labeled protein A. Either peripheral myelin proteins or purified PO may be used as the antigen. Optimal extraction of tissue samples for PO immunoassay requires careful attention to the sodium dodecyl sulfate-to-protein ratio. Sodium dodecyl sulfate interference with antibody binding can be minimized by adding an excess of nonionic detergent and carrier pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…Although increased amounts of endoneurial connective tissue have been described (Ayers & Anderson, 1973;Low & McLeod, 1975; * To whom correspondence should be addressed 1983), the pathology emerges in the absence of the Trembler connective tissue environment (Bunge et al, 1980;Mithen et al, 1982). Biochemical analyses have demonstrated decreased levels of myelin-related lipids (Larrouquere-Regnier et al, 1979) and proteins including P0, myelin basic protein (MBP) and 2',3'-cyclic nucleotide 3'-phophodiesterase (CNP) (Bourre et al, 1982;Fryxell et al, 1983;Jacque et al, 1983;Lewis et al, 1984;Inuzuka et al, 1985). Although the level of myelin associated glycoprotein (MAG) is not reduced, an abnormal high molecular weight form is present in the PNS, and may contribute to the failure of normal myelin compaction (Inuzuka et al, 1985).…”
Section: Introductionmentioning
confidence: 94%
“…Although increased amounts of endoneurial connective tissue have been described (Ayers & Anderson, 1973;Low & McLeod, 1975; * To whom correspondence should be addressed 1983), the pathology emerges in the absence of the Trembler connective tissue environment (Bunge et al, 1980;Mithen et al, 1982). Biochemical analyses have demonstrated decreased levels of myelin-related lipids (Larrouquere-Regnier et al, 1979) and proteins including P0, myelin basic protein (MBP) and 2',3'-cyclic nucleotide 3'-phophodiesterase (CNP) (Bourre et al, 1982;Fryxell et al, 1983;Jacque et al, 1983;Lewis et al, 1984;Inuzuka et al, 1985). Although the level of myelin associated glycoprotein (MAG) is not reduced, an abnormal high molecular weight form is present in the PNS, and may contribute to the failure of normal myelin compaction (Inuzuka et al, 1985).…”
Section: Introductionmentioning
confidence: 94%
“…Schwann cells grown in culture are capable of active assembly of extracellular matrix and myelin only if they are in contact with axons and are provided serum or ascorbic acid (Carey et al, 1986;Carey and Todd, 1987;Eldridge et al, 1987). Primary Schwann cell cultures undergo mitosis but do not seem to express immunologically detectable levels of myelin antigens (Raff et al, 1979;Brockes et al, 1980Brockes et al, , 1981Mirsky et al, 1980;Fryxell et al, 1983) and certain matrix components . Unlike cells from transected adult nerve in vivo (Poduslo, 1984LeBlanc et al, 1987) or in culture (Poduslo and Windebank, 1985), previous work has suggested that neonatal Schwann cells appear to revert completely to a progenitor state after culture where they are incapable of any expression of Po (Poduslo and Windebank, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal Schwann cells grown in culture without the effect of axons are incapable of differentiation to a stage that demonstrates basal lamina production and myelin assembly (Bunge et al, 1982). Whereas neonatal Schwann cells are in an actively myelinating state in vivo, the explanted cells appear to lose the ability to produce myelin-specific proteins and lipids (Raff et al, 1979;Brockes et al, 1980Brockes et al, , 1981Mirsky et al, 1980;Fryxell et al, 1983), as well as extracellular matrix components (Cornbrooks et al, 1981;Carey et al, 1983), unless axonal contact is reinitiated. Examination of the level of production of the major myelin glycoprotein, Po, by neonatal Schwann cell explant cultures from 4-day-old rat reveals no detectable de novo synthesis (Poduslo and Windebank, 1985).…”
mentioning
confidence: 99%
“…Trapp et al (1979), Brockes et al (1980), and Ishaque et al (1980) raised antisera against the PO antigen, but most of their reported studies with these materials were immunocytochemical. While this manuscript was under revision a paper by Fryxell et al (1983) was published describing the development and applications of a solid-phase immunoassay for the PO protein based on a standard solid-phase immunoassay method.…”
Section: Discussionmentioning
confidence: 99%